COVID-19 Pandemic and Oral and Maxillofacial Surgery - O.A. Akadiri; K.S. Yarhere (Nigerian Dental Association, 2020)
Objective: To present a brief overview of global adjustments to COVID-19 by oral and maxillofacial surgeons and to characterise the reactions and adaptations of the oral and maxillofacial surgery specialty in Nigeria. Materials and Methods: A review of the global literature was done to highlight available guidelines for oral and maxillofacial surgery under COVID-19 pandemic. Questionnaires were electronically sent to maxillofacial surgeons in Nigeria and, a telephone survey of the Nigerian oral and maxillofacial surgery centres was done to characterise the reactions and adaptations of local practitioners to the pandemic situation. Results: Out of the 822 questionnaires electronically delivered to maxillofacial surgeons across 156 centres worldwide, the response rate was only 20.2%. Twenty-eight (17.9%) centres were completely shut down while only 6 (3.8%) centres were functioning normally. Other centres scaled down services and/or number of personnel. Surgeons older than 60 years were made to stay away in some centres while some personnel were drafted to support the medical team at the frontline COVID-19 treatment centres. Conclusion: It concluded that the variability of practices is remarkable and this is largely due to unequitable resources and lack of uniform policies even among federal tertiary health institutions and the authors therefore proposed an algorithm to guide oral and maxillofacial patients' classification and management in the face of COVID-19 pandemic.